A gender-transformative response to COVID-19 in Myanmar - Lambrecht, Isabel B.; Mahrt, Kristi; Ragasa, Catherine; Wang, Michael; Ei Win, Hnin; Win, Khin Zin (International Food Policy Research Institute, 2020)
On 27 April, the Myanmar Government published the COVID-19 Economic Relief Plan (CERP) which aims to mitigate COVID-19’s impact on the macroeconomic environment and the private sector and to ease the impact on laborers, workers, and households. The CERP action plan should pay explicit attention to gender discrepancies to avoid unintentional harm or aggravating existing gender inequalities.